NATIONAL FORMS OF BODY ICONOTROPIZATION IN MODERN POLISH AND UKRAINIAN ARTISTIC DISCOURSE - Vasylkiv, Halyna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article examines the forms of bodily iconotropization through the prism of their representation in national ethnic codes embodied in contemporary Polish and Ukrainian postmodern discourse. The object of the research is the novel "Solodka Darusia" by Maria Mathios and "Pravik and other times" by Olga Tokarchuk. The selected works make it possible to explore the topic in detail, since the representations of the physical characters in both novels are connected with the national matrix and the characteristic ethnocode of Polish and Ukrainian cultures. The subject of analysis is the bodily elements of the heroes represented in the novels. Among the research methods - comparative, which in our research is based on the comparison of selected novels in the context of the national characteristics of Polish and Ukrainian culture. The comparative method is relevant in the study of postmodern literature, because in the modern world globalization brings cultures closer together. We can determine the important role of the hermeneutic approach in the study of the poetics of iconotropism in the work of the selected women writers, in particular the integrity of images, since both novels tell about the period from the beginning of the 20th century, but nevertheless with a projection on the modern world. Also important are the formal and typological methods that contribute to the determination of the systemic, structural principles of bodily iconotropism in the Ukrainian and Polish literary traditions. As a result, on the basis of the selected novels, a two-way connection between the body and the national can be traced, which in a certain way iconotropizes the "body of the nation". Similar and distinctive features of the iconotropization of body elements in the characters' images are analyzed. Such an analysis helps to trace the iconic-conventional features of ethnic semiotics in a specific context. The identified tasks and conclusions are relevant for modern trends in European science. Having analyzed individual aspects of the investigated problem, we can conclude that national physicality is a complete system. This is due to cultural traditions, religious beliefs and historical background. The analysis of the iconotropism of corporeality through the prism of representation in national ethnic codes, embodied in creativity, provides a deeper understanding of the relationship between the internal and external levels. We see a certain similarity between the Polish and Ukrainian nations in the intentions of iconotropization of such an abstract element as the soul, which is connected with the dominance of religion in the cultural environment of both nations. We also trace the important role of the relationship between nature and the human body. In the Ukrainian and Polish national consciousness, nature is perceived as a separate living organism from which man draws strength and energy. Instead, the embodiment of the female braid in Ukrainian literature, which is a consequence of the traditional worldview, seems to be excellent. Such an analysis helps to trace the ethnic characteristics of a certain community. Such scientific research is extremely important in the light of modern trends in European culture.